Rock Compressibility Characteristics of Oil and Gas Sandstone Reservoirs in the Western Part of Indonesia - Widarsono, Bambang; Musu, Junita T.; Yohanes, Yohanes D. Wangge (Scientific Contributions Oil and Gas, 2025)
Rock compressibility is one of rocks’ properties that is closely related to their response to changes in effective stresses. Various Earth’s subsurface-related processes involve rock compressibility. In petroleum production, for instance, it provides reservoir energy needed for the process. Studies on rock compressibility for Indonesian reservoirs are very limited. Therefore, a study has been carried out to investigate rock compressibility characteristics of Indonesian reservoir rocks, sandstones in particular. A total of 205 sandstone samples of various types have been collected from 34 oil/gas fields in nine productive sedimentary basins in Indonesia. The samples are prepared and laboratory tested for their basic properties and pore volume compressibility following the universally adopted standard methods. Results of this study indicate unclear trends in the rock property of concern in relation to porosity. However, with careful grouping and cluster analyses, clearer trends representing their intrinsic characteristics can be spotted, and appropriate correlations based on a generalized model can be established. The established correlations of maximum effective rock compressibility versus porosity offer opportunities to understand the characteristics of reservoir sandstone compressibility. Special cautions have been discussed, and special suggestions have also been offered for selecting the most appropriate correlations.